Gender Differences in Neurocognitive Performance Among Children With Posttraumatic Stress Disorder and Mild Traumatic Brain Injury. Issue 1 (1st February 2018) - Segev, Shira; Shorer, Maayan; Peleg, Tammy Pilowsky; Apter, Alan; Fennig, Silvana; Rassovsky, Yuri
Abstract: Posttraumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI) are frequent sequelae after motor vehicle accidents (MVAs). These two pathologies often have overlapping neurocognitive deficits across several domains, such as attention, memory, and executive functions. The present study was an effort to examine the contribution of gender to these overlapping symptoms. To this end, psychodiagnostic and neuropsychological data were collected on 61 children and adolescents 3 months following MVA. All participants were diagnosed with PTSD, and about half ( n = 33) also received a diagnosis of mTBI. Analyses of variance revealed significant interactions between gender and mTBI ( η p 2 = . 15 ), such that girls with mTBIs preformed significantly worse than noninjured girls on measures of executive functions (Cohen's d = 3.88) and sustained attention (Cohen's d = 3.24). Boys, on the other hand, did not differ significantly on any of those measures, irrespective of TBI injury status. Similarly, comparisons to the normative population revealed that, whereas boys showed impaired neurocognitive performances regardless of TBI status, impaired performances in girls were limited to those cases in which the girls were comorbid for PTSD and mTBI. It appears then that whereas PTSD alone might explain boys' reduced neurocognitive performance, among girls the comorbidity of PTSD and mTBI is required to account for performance deficits.